Energizing the Inter-regional Cooperation and Energy Governance: An Exploration of the Africa-EU Energy Partnership - Afeez Adiatu (Journal of Sustainable Development of Energy, Water and Environment Systems, 2024)

(untitled)
The emergence of change in the global energy governance structure is precipitated by the shift in global energy technology. The shift from carbon-intense energy to cleaner sources surpasses technological discontinuation. The inter-regional, regional, and sub-regional grouping emerged in global energy governance to support governance capabilities across countries. This research seeks to investigate the inter-regional partnership between Africa and the European Union initiated to facilitate energy decision-making. This study adopts thematic analysis to explore literature and reports on the Africa-EU partnership to understand its impact on the future of the African energy sector. This research argues using a neo-liberal lens that the limited state capacity in energy governance may necessitate inter-regional partnerships to aid energy sector development in Africa. The study concludes that considering Africa's potential in renewable energy sources such as solar irradiation and the limited energy access in the Sub-Saharan region, intervention of external capabilities through technological and financial aids may stimulate the utilization of such potential.